Instant Messaging in Dental Education. Issue 12 (1st December 2015) - Khatoon, Binish; Hill, Kirsty B.; Walmsley, A. Damien
Abstract : Instant messaging (IM) is when users communicate instantly via their mobile devices, and it has become one of the most preferred choices of tools to communicate amongst health professions students. The aim of this study was to understand how dental students communicate via IM, faculty members' perspectives on using IM to communicate with students, and whether such tools are useful in the learning environment. After free‐associating themes on online communication, two draft topic guides for structured interviews were designed that focussed on mobile device‐related communication activities. A total of 20 students and six faculty members at the University of Birmingham School of Dentistry agreed to take part in the interviews. Students were selected from years 1–5 representing each year group. The most preferred communication tools were emails, social networking, and IM. Emails were used for more formal messages, and IM and social networking sites were used for shorter messages. WhatsApp was the most used IM app because of its popular features such as being able to check if recipients have read and received messages and group work. The students reported that changes were necessary to improve their communication with faculty members. The faculty members reported having mixed feelings toward the use of IM to communicate with students. The students wished to make such tools a permanent part of their learning environment, but only with the approval of faculty members. The faculty members were willing to accept IM as a communication tool only if it is monitored and maintained by the university and has a positive effect on learning.